2013
DOI: 10.1007/s11051-013-1679-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of methyl blue onto magnetic Ni0.5Zn0.5Fe2O4 nanoparticles prepared by the rapid combustion process

Abstract: A rapid combustion process for the preparation of magnetic Mn 0.5 Co 0.5 Fe 2 O 4 nanoparticles was introduced, which was composed of the preparation process of solution, combustion process and calcination process. The structure and properties of the as-prepared product were investigated by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and vibrating sample magnetometer. The results revealed that the volume of absolute alcohol and the calcination temperature were two key par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Similar kinetic results were also obtained by He et al who performed the sorption of Congo red onto magnetic MnFe 2 O 3 nanosheets. Liu et al also reported similar phenomena in case of removal study of methyl blue onto magnetic Mn 0.5 Co 0.5 Fe 2 O 4 ·NPs.…”
Section: Resultssupporting
confidence: 54%
“…Similar kinetic results were also obtained by He et al who performed the sorption of Congo red onto magnetic MnFe 2 O 3 nanosheets. Liu et al also reported similar phenomena in case of removal study of methyl blue onto magnetic Mn 0.5 Co 0.5 Fe 2 O 4 ·NPs.…”
Section: Resultssupporting
confidence: 54%
“…Such results attested the potential use of these promising materials, which can be easily prepared from inexpensive and abundant materials for the removal of recalcitrant contaminants in water and waste waters. Magnetic nanoparticles 45 and/or TiO 2 46 can be readily prepared and incorporated into carbon monoliths via adsorption to facilitate the process design and perform both adsorption and photocatalytic remediation of this blue dye as well as other organic pollutants.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Many reports on the adsorption of anionic dyes in aqueous media using various adsorbents are successfully applied in batch processing for removal of dyes [19,20,21,22,33,34,35,36,37,38,39]. However, these processes frequently require an additional process to separate the solid adsorbents from the water after the purification procedure is finished.…”
Section: Resultsmentioning
confidence: 99%